1988
DOI: 10.1159/000217561
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Thomsen-Friedenreich Antigens during Tumor Progression in Breast Cancer Patients

Abstract: Paraffin-embedded tissue sections of primary tumors and lymph node metastases of 80 breast cancer patients were tested for the expression of Thomsen-Friedenreich (TF) antigens with the aid of a monoclonal IgM antibody (49H8) highly specific for phenyl-beta-galactoside. TF antigens were not expressed in 16 different normal tissues with the exception of some structures in the kidney. In tumor cells, two types of antigen expression were found; namely, cryptic and exposed. From stage T1/No to stages T2–4/N1,2 the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 8 publications
1
21
1
Order By: Relevance
“…This discrepancy probably reflects the different sensitivities of antibodies and lectins used in most studies [12,17,25,27]. We found T antigen expression not only in morphologically normal epithelial cells adjacent to carcinomas as shown by Reed et al .…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…This discrepancy probably reflects the different sensitivities of antibodies and lectins used in most studies [12,17,25,27]. We found T antigen expression not only in morphologically normal epithelial cells adjacent to carcinomas as shown by Reed et al .…”
Section: Discussionmentioning
confidence: 46%
“…The demonstration of T (Thomsen-Friedenreich) antigen in breast epithelium is variable from series to series [12,17,25,27]. This discrepancy probably reflects the different sensitivities of antibodies and lectins used in most studies [12,17,25,27].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TF expression was always accompanied with MUC1 expression suggesting that MUC1 is the carrier protein for TF also in DTC-BM. Surprisingly, 98% of all DTC-BM found by CK staining were also positive for TF, although only 40-70% of invasive primary breast cancers are positive for this antigen (Wolf et al 1988). In that study, the number of cases expressing high amounts of TF antigens increased from 9% in stage T1/N0 to 22% in stage T2-4/N1,2.…”
Section: Discussionmentioning
confidence: 66%
“…In several tumor entities, for example gastric, colon (Baldus et al 2000), lung (Takanami 1999) or cancer of the cervix uteri (Hirao et al 1993), a correlation between TF expression and negative prognosis could be demonstrated. Also in breast cancer, a correlation between high tumor stage and TF expression was observed (Wolf et al 1988) and TF expression predicted worse survival (Imai et al 2001). Results obtained in our study show that TF is also expressed on DTC-BM of breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, its prognostic impact in other tumors, especially in breast cancer, is indeterminate. A correlation between high tumor stage and TF expression was observed [24], whereas in another study high TF expression predicted improved survival [25].…”
Section: Introductionmentioning
confidence: 99%